Diaspora as a Generator of Foreign Direct Investment - Dizdarević, Emina (IUS LAW Journal, 2024)
Focusing on Bosnia and Herzegovina, this study examines how diasporas contribute to the creation of foreign direct investment (FDI) in developing countries. It defines FDI as the acquirement over assets in a foreign nation and highlights how diaspora populations support investment flows. It also examines diaspora investment strategies, such as diaspora portfolio investment (DPI) and diaspora direct investment (DDI), and offers a historical overview of diaspora FDI patterns and how Bosnia and Herzegovina's policies are changing to engage its diaspora more.One case study illustrates the impact of diaspora-led FDI by highlighting the success of Senad Šantić, a Bosnian entrepreneur who returned to his home country to start a tech company. While these investments support development and economic growth, there are still issues, like the possibility of putting one's own interests ahead of the interests of the economy as a whole. Particularly in Bosnia and Herzegovina, where diaspora participation has historically been low, the implementation of effective policies and procedures is crucial, especially from a regulation perspective.The study also looks at the future of FDI, emphasizing the part that digital technology and new investment patterns will play. Opportunities for developing nations can be found in digital FDI, especially in industries like fintech and e-commerce, yet obstacles still exist in luring these investments. According to all the findings, developing nations can improve their chances for economic success by creating an atmosphere that encourages diaspora investment which will shift those nations into the global investment scene. Ultimately, FDI regulations and government programs are needed in order to fully utilize diaspora-led FDI for sustained growth.
Keywords: Bosnia and Herzegovina; Diaspora Engagement; Diaspora Investment; Economic Development; FDI; Foreign direct investment

Business Environment and its Impact on Attracting Foreign Direct Investment - Tanrıverdi, Elif Tanrıverdi (IUS LAW Journal, 2024)
This study provides an in-depth look at the complex relationship between business environments and foreign direct investment. The study examines this critical issue by focusing on emerging economies, such as Kosovo. In this research, analytical and empirical research methods have used to highlight the importance of FDI in promoting economic growth. FDI not only increases production capacity but also supports economic growth by increasing purchasing power and creating employment opportunities, especially in countries in transition. This analysis distinguishes between endogenous and exogenous variables to classify the various elements of the business environment. It is important to emphasize how a supportive business environment plays a vital role in attracting investment. The main factors affecting FDI include infrastructure quality, political stability, workforce skills, market potential and tax incentives. These initiatives are critical to creating a more favorable investment climate.As a result of the variables the study concludes by emphasizing the need for continuous reforms to strengthen the business environment. Such strategic efforts are crucial to optimize FDI flows and advance sustainable economic development. By strengthening regulatory frameworks and improving infrastructure, developing countries can be in better position itself to attract foreign investors. Furthermore, creating a strong business environment can also support the development of local entrepreneurs, increasing economic diversification. As a result, it not only facilitates the flow of capital, but also contributes to the long-term stability and growth of the national economy. Therefore, policymakers and governments need to prioritize these initiatives and develop comprehensive and sustainable strategies to improve the business environment.
Keywords: Business Environment; Economic growth; Foreign direct investment; Investment Incentives; Investments; Political Stability

Anticipation of ratings during crises and investor behaviour: The case of MENA countries - Mahouachi, Noura; Henchiri, Jamel Eddine (African Journal of Economic and Business Research, 2024)
The study explores the reaction of stock markets to anticipated or unexpected rating announcements by the market in a crisis context by conducting an empirical study on the MENA (Middle East and North Africa) stock market over the period from December 2010 to August 2022. The results show that the crisis context support the anticipation of bad ratings and neutral ratings as opposed to good ratings. These results validate the asymmetry in investor reaction to announcements of anticipated rating downgrades compared with announcements of upgrades in times of crisis. This reaction highlights the irrational behave of investors in times of crisis. In fact, when investors detect a risk concerning the financial situation of a stock, they anticipate a downgrade and react quickly, even before the official announcement of the downgrade, by selling their shares on masse. This action will cause the share price to fall. Similarly, the market’s weak reaction to early good announcements is explained by the fact that this type of announcement does not provide them with any unknown information to guide their financial decisions.
Keywords: Abnormal returns; Anticipation; Event study; Expected rating; Stock markets; Unexpected rating

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Le traitement des investissements étrangers dans le Code des investissements de la RDC de 2002 - Nzohabonayo, Anaclet (Revue africaine de droit des affaires, 2024)
Cet article examine le traitement que le code des investissements de la République démocratique du Congo garantit aux investisseurs étrangers qui choisissent ce pays comme destination de leurs investissements. L’étude examine d’abord la portée dudit code en articulant son analyse sur sa philosophie afin de dégager les motivations du législateur et les objectifs que ce dernier lui a assignés. L’examen du champ d’application du code met l’accent sur sa portée ratione personae, ratione materiae et ratione loci. La réflexion explore ensuite les principaux mécanismes de traitement des investissements en démontrant que le code consacre un traitement non discriminatoire envers les investisseurs étrangers et qu’il adhère à l’orthodoxie des normes classiques de protection des investissements. L’étude analyse par ailleurs les incitatifs fiscaux et douaniers que le code concède aux investisseurs étrangers afin d’accroître la compétitivité de la destination congolaise parmi les investisseurs exportateurs de capitaux. Après analyse, l’étude conclut qu’en dépit de ses imperfections que nos analyses ont permis de mettre en lumière, le code des investissements de 2002 offre aux investisseurs étrangers un traitement globalement satisfaisant.
Keywords: Congo (République démocratique); Investissements; Investments

Comportement d’investissement des entreprises camerounaises : analyse en données de panel 2015-2022 - Metangmo, Janvier; Nankap Seujib, Alexis (Finance & Finance Internationale, 2024)
L’objectif de cette étude est de déterminer les facteurs influençant le comportement d’investissement des entreprises camerounaises par une approche microéconomique. En effet, malgré un taux de profit élevé (l’EBE représente environ 60% de la valeur ajoutée), le taux d'investissement privé au Cameroun demeure très faible (18% du PIB) et risque de compromettre l'atteinte du stade de pays émergent à l'horizon 2035. En se basant sur le modèle théorique accélérateur-profit, nous avons estimé un modèle de panel dynamique grâce aux données de 381 entreprises sur la période 2015-2022, par la méthode des moments généralisés (GMM). Les résultats obtenus identifient la demande sur le marché (effet accélérateur) comme principal facteur qui agit positivement et significativement sur l’investissement. A contrario, le profit, la dette ou les capitaux propres n’ont pas une influence significative sur le comportement d’investissement des entreprises camerounaises. En outre, même en cas de demande importante, le comportement d’investissement des entreprises camerounaises est influencé par leur statut juridique, leur taille, leur activité principale et l’état sécuritaire de la zone d’implantation. Cela illustre à souhait l’importance d’améliorer l’environnement des affaires et d’encourager les entreprises camerounaises à muter vers des modes d’organisation leur garantissant non seulement un développement rapide mais aussi une pérennisation. The aim of this study is to determine the factors influencing the investment behavior of Cameroonian companies, using a microeconomic approach. Indeed, despite a high profit rate (EBITDA represents around 60% of value added), the private investment rate remains very low (18% of GDP) and risks compromising the country's ability to reach the stage of an emerging country by 2035. The covid 19 crisis, the Boko Haram security crisis in the northern part of the country and the secessionist crisis in the English-speaking regions all add to an already unfavourable business climate. These observations lead us to reflect further on the factors that explain the investment behavior of Cameroonian companies. Based on the theoretical accelerator-profit model, we estimated a dynamic panel model using data from 381 companies over the period 2015-2022, using the generalized method of moments (GMM). The results obtained identify market demand (accelerator-effect) as the main factor acting positively and significantly on investment. Conversely, profit, debt or equity do not have a significant influence on the investment behavior of Cameroonian companies. Other variables such as the company's legal status, size and activity also have an effect on investment. The company's geographical location in a zone of insecurity, such as the northern and western regions of Cameroon, also has a negative effect on investment behavior, no doubt due to the uncertainty and irreversible nature of the investment.
Keywords: Accelerator-profit model; Cameroon; Cameroun; Effet de levier; Entreprises; Firms; GMM; Investissements; Investments; Modèle accélérateur-profit; Q de Tobin; Tobin's Q

La réforme des dommages dans le règlement des différends entre investisseurs et États et la question de la réparation intégrale - Marzal, Toni (Investment Treaty News, 2024)
Keywords: Dispute resolutions; Dispute settlement; Investissements; Investments; Règlement des différends

L’intérêt du développement dans les accords de promotion et de protection des investissements - Nyeck, Emmanuel Noé (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La conclusion des accords de promotion et de protection des investissements a pour fonction d’augmenter significativement les investissements directs étrangers dans les pays en développement afin de les sortir du sous-développement. Ces accords sont donc envisagés comme la panacée contre le sous-développement en raison de l’échec des solutions traditionnelles de lutte contre le sous-développement. Cependant, fort est de constater que le développement auxquels ils renvoient ne peut être élevé au rang d’une véritable obligation juridique dans la mesure où la notion de développement est elle-même est ancré dans la soft law.
Keywords: Bilateral Investment Treaties (BITs); Contentieux de l’investissement; Droit international de l’investissement; Droit international du développement; Droits de l’homme; Human rights; International Investment Law; International development law; Investment litigation; Traités bilatéraux des investissements

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Vulnerability Theory as a Paradigm Shift in International Investment Law: Reimagining the Role of the State - Küçüksu, Aysel; Ünüvar, Günes (Business and Human Rights Journal, 2023)
This article argues for a fundamental raison d'être reconceptualization of international investment law (IIL) through Martha Fineman's 'vulnerability theory'. The theory helps identify the structural sources of IIL's shortcomings, whilst philosophically challenging the one-sided view that foreign investors are entitled to protections, but are free from obligations vis-à-vis the communities affected by their undertakings. Emphasizing the productive power of the state to take positive action that acknowledges ordinary citizens' embeddedness within, and dependence upon, surrounding structures, the vulnerability theory challenges the hegemonic perception of the state as a source of danger - a view which has hitherto undermined both the potency and the enforceability of investor obligations. Used as a heuristic device in studying both IIL's existing structures and the potential avenues for reimagining it, Fineman's theory not only shines a novel light on the foundational premises of IIL, but also grants theoretical traction to existing ideas about improving the system.

Congolese Land Rights Put to the Test by the Private Real Estate Investment Revolution - Milenge, Christian Mwenyemali (Open Journal of Social Sciences, 2023)
Private investors’ land rights vary from country to country, depending on the legal system in place. The degree of openness of land laws determines the degree to which both domestic and foreign investors are attracted, as the latter aims to invest in countries with legal systems offering the most secure and sustainable interests. How can Congolese land laws be made more attractive to private investors in the real estate sector? Using exegetical and comparative methods, we will test our hypothesis that reform to increase the rights of private national and foreign investors to access land would be an asset. By comparing Congolese land law with other legal systems, and with current social and economic realities, we have concluded that accommodating land rights is a prerequisite for increasing both domestic and foreign private investment in real estate and an essential step towards boosting and modernizing real estate investment in the DRC.
Keywords: Agricultural Investment; Congolese Land Ownership Law; Investments; Land Rights; Private Investment; Real Estate Law

Legal Framework on Protection of Environmental and Foreign Direct Investment Rights in Nigeria: A Reflection on the Oil and Gas Industry - Osaro, Ebiemere (African Journal of International Energy & Environmental Law, 2023)
It is trite that environmental challenges remain one of the major global concerns and no doubt of great impact on human existence and wellbeing. This impact is a result of human activities on the natural ecosystem. This article examines the legal framework by the Nigerian state in regulating the activities of the multinational investors in the oil and gas industry in the Niger Delta region of the country. It discusses the international, regional, and national legal framework in the protection of environment and environmental rights of the host community and foreign direct investment rights. The author demonstrates the imbalance in the protection of environmental and foreign direct investment rights from which suggestions are made towards correcting this injustice as caused by the existing legal framework.
Keywords: Community; Direct; Environment; Foreign investment; Niger Delta; Oil and Gas Industry; Protection; Rights

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

Investissements directs étrangers et croissance économique : une analyse empirique des données de l’Afrique des Grands Lacs - Selenge, Bienvenu Mulunda; Kasongo, Maxime Mukwamba (Repères et Perspectives Economiques, 2022)
L’objectif de cet article est d’identifier, dans le cas spécifique des pays de l’Afrique des Grands Lacs, les canaux de transmission par lesquels les flux entrants d’investissements directs étrangers (IDE) peuvent avoir une influence positive sur la croissance économique.  Nous employons à la fois la méthode des moindres carrés généralisés simple (MCG) et la méthode des moindres carrés généralisés réalisables (MCGR) pour vérifier l’évidence empirique de cette relation, entre les IDE et la croissance, sur les données de la période 1970-2019. Les résultats montrent que les IDE ont un impact positif sur la croissance économique, mais qui dépend fortement de la stabilité macroéconomique. D’autre part, nous ne trouvons pas l’incidence des facteurs tels que le développement financier, l’ouverture commerciale et le capital humain comme canaux de transmission de l’effet positif des IDE sur la croissance.
Keywords: Afrique des Grands Lacs; Croissance économique; FDI; Foreign direct investment; Investissements directs étrangers; Stabilité macroéconomique

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

Investment Law and its Others - Schneiderman, David (Temple International Law Journal, 2022)

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

Scope of Obligation of the Host State for Protection of Foreign Investor in Armed Conflicts - Shahbazian, Abolghasem; Salimi, Sadegh (Public Law Researsh, 2022)
Measures taken by governments during armed conflict to safeguard their essential interests sometimes cause damages to foreign investors. The investors thus affected seek remedies in the arbitration tribunals invoking breach of host government obligations to protect investments. The host government also usually attempts to assert as defense non-precluded measures to prove its irresponsibility, or if it proves responsible, justify it by resorting to circumstances precluding wrongfulness in the customary international law. But since different courts do not consider the same requirements to invoke these rules, there is no certainty that the parties to the lawsuit will be able to invoke them and, as a result, the scope of government's obligations to protect the foreign investor during the armed conflict is obscure. To clarify the scope of the host government's obligations to protect the foreign investor during armed conflicts and balance the interests of the investor and the host government during the investment disputes arising from the armed conflict, this article explores the possibility and requirements of invoking circumstances precluding wrongfulness and non-precluded measures and the relationship between them. اقداماتی که دولت‌ها در زمان مخاصمات مسلحانه در جهت حفظ منافع اساسی خود انجام می‌دهند گاه موجب ورود خسارت به سرمایه‌گذاران خارجی می‌گردد. سرمایه‌گذاران آسیب‌دیده در محاکم داوری با استناد به نقض تعهدات حمایتی توسط دولت میزبان، خسارات وارده به خود را طلب می‌نمایند. دولت میزبان نیز معمولاً برای اثبات عدم مسئولیت خود به شرط اقدامات منع نشده مندرج در معاهده سرمایه‌گذاری استناد می‌کند و یا در صورت اثبات مسئولیت، به منظور توجیه آن به معاذیر رافع وصف متخلفانه در حقوق بین‌الملل عرفی متوسل می‌شود. اما از آنجا که محاکم مختلف، شرایط یکسانی را جهت استناد کشور میزبان به شرط اقدامات منع نشده و معاذیر رافع وصف متخلفانه در نظر نمی‌گیرند، قطعیتی در امکان استناد به آن‌ها وجود ندارد. در نتیجه، قلمرو تعهد دولت به حمایت از سرمایه‌گذار خارجی در زمان مخاصمات مسلحانه در هاله‌ای از ابهام فرو رفته است. این مقاله با هدف روشن ساختن قلمرو تعهد دولت میزبان به حفاظت از سرمایه‌گذار خارجی در هنگام مخاصمات مسلحانه و به منظور توازن منافع سرمایه‌گذار و دولت میزبان در دعاوی سرمایه‌گذاری ناشی از مخاصمات مسلحانه، امکان و الزامات استناد کشور میزبان به معاذیر عرفی رافع وصف متخلفانه و شرط اقدامات منع نشده و ارتباط میان آنها را مشخص می‌نماید
Keywords: Armed Conflicts; Customary International Law; Foreign investment; Interests of the Host State; Non-Precluded Measures; اقدامات منع نشده; حقوق بین‌الملل عرفی; سرمایه‌گذاری خارجی; مخاصمات مسلحانه; منافع دولت میزبان

The Relationship between International and Domestic Law in the Field of Attribution of Responsibility to a State in International Investment Disputes - Amidimehr, Elham; Seifi, Jamal (Public Law Researsh, 2021)
The attributability of actions to states within the context of investment treaty disputes and to focus on the roles played by international and domestic laws in such attributions have caught the attention of jurists in recent years. The ILC Draft Articles on Responsibility of States for Internationally Wrongful Acts, and particularly, article 3 points to the main outcome of this debate, where it does not consider domestic law irrelevant in internationally wrongful acts and stipulates that the issue is subject to international law and it will take into account the relevance of domestic law. Thus, although the characterization of an act of a State as internationally wrongful is an independent function of international law and such characterization is not affected by the characterization of the same act as lawful by domestic law, it does not mean that domestic law is irrelevant to such description; on the contrary, it may be related in various ways. The present article attempts to examine the challenging junction of domestic and international law with regard to the attributability of actions taken within the framework of investment treaties, specifically by state-owned and para-statal entities that exercise elements of state authority. قابلیت انتساب عمل به دولت در چارچوب اختلافات معاهده‌ سرمایه‌گذاری و تمرکز بر نقش‌هایی که حقوق بین‌الملل و حقوق داخلی در چنین انتسابی ایفا ‌می‌نمایند در زمره‌ مباحثی است که در سال‌های اخیر بسیار مورد ‌توجه حقوقدانان بوده و ماده 3 مواد کمیسیون حقوق بین‌الملل در ارتباط با مسئولیت دولت‌ها نیز بیانگر پیامد اصلی این بحث است که فی‌الواقع، حقوق داخلی را با مسأله متخلفانه بودن اعمال از حیث بین‌المللی بی‌ارتباط تلقی ‌ننموده، بلکه مقرر ‌می‌دارد مسئله مورد بحث، تابع حقوق بین‌الملل است لیکن حقوق بین‌الملل نیز خود تا حدِ ارتباط، حقوق داخلی را در نظر خواهد گرفت. بنابراین اگرچه توصیف خصوصیات یک عمل به عنوان عملی غیرقانونی از عملکردهای مستقل حقوق بین‌الملل است که تحت ‌تأثیر توصیف خصوصیات این عمل بموجب حقوق داخلی قرار نمی‌گیرد لیکن این گفته بدین معنی نیست که حقوق داخلی با توصیف عمل متخلفانه‌ بین‌المللی بی‌ارتباط ‌است؛ بالعکس، ممکن ‌است به طرق مختلفی به آن مرتبط‌ باشد. در این مقاله سعی بر‌ آن است که تلاقی چالش‌برانگیز حقوق داخلی و حقوق بین‌الملل در بحث قابلیت انتساب اعمال ‌صورت ‌گرفته در چارچوب معاهدات سرمایه‌گذاری توسط ارگان‌های دولتی و نهادهای نیمه‌دولتی که عناصر اختیارات دولتی را اعمال می‌نمایند مورد واکاوی قرار‌ گیرد.
Keywords: Attribution; Domestic Law; International Arbitration; International Investment Treaties; International Law; حقوق بین‌الملل; حقوق داخلی; داوری بین‌المللی; معاهدات سرمایه‌گذاری بین‌المللی; کلیدواژگان انتساب مسئولیت

A Reflection on the Invalidation of Patents in the Light of Constituent Elements of Indirect Expropriation under Foreign Investment Law - Rahbari, Ebrahim; Shahabi, Mahdi; Falahati, Soroosh (Public Law Researsh, 2021)
Patents are considered as investments protected under the International Investment Law. Although, these properties are protected under the principle of territoriality, similar to other investments, they can be expropriated as a result of host states’ regulatory measures inconsistent with protection standards stemming from foreign investment protection regulations and treaties including fair and equitable treatment and legitimate expectations of foreign investors. Considering the fact that few arbitration awards have been issued by arbitration panels in this regard, it is yet difficult to claim there is a strong precedent in International Investment Law. Nevertheless, reflecting the provisions of international regulations, the stance of the domestic law and the most important relevant case, this article provides the most significant elements of indirect expropriation as well as existing doctrines in this respect and further investigates whether invalidation of patents can amount to indirect expropriation. It will also be mentioned that despite the fact that according to several foreign investment protection treaties, invalidation of patents shall not be subject to regulations regarding indirect or creeping expropriation, the final determination lies with the arbitration panel. یکی از مصادیق سرمایه‌گذاری خارجی مورد حمایت در حقوق بین‌الملل سرمایه‌گذاری، اختراعات است. این دسته از دارایی‌ها علی‌رغم به رسمیت شناخته شدن در پرتو اصل سرزمینی بودن حمایت، همانند سایر سرمایه‌گذاری‌ها می‌توانند تحت تدابیر حاکمیتی دول میزبان که مغایر با استانداردهای حمایتی نشأت گرفته از قوانین و معاهدات بین‌المللی حمایت از سرمایه‌گذاری خارجی همچون شرط رفتار عادلانه و منصفانه و صیانت از انتظارات مشروع و معقول سرمایه‌گذار می‌باشند، با خطراتی همچون سلب مالکیت مواجه شوند. نظر به صدور آرای معدود مراجع بین‌المللی در این خصوص، سخن گفتن از شکل‌گیری رویه‌ای متقن در این راستا دشوار می‌باشد. با این حال، در این نوشتار ضمن بررسی مهمترین عناصر متشکله سلب مالکیت غیرمستقیم و دکترین‌های موجود در این زمینه، به بررسی قابلیت تطبیق ابطال گواهی ثبت اختراع با سلب مالکیت غیرمستقیم پرداخته و با تشریح مقررات برخی اسناد بین‌المللی، موضع حقوق داخلی و مهم‌ترین پرونده مربوط به این موضوع در حقوق سرمایه‌گذاری خارجی در ابعاد گوناگون آن مداقه نموده و در نهایت به این نتیجه خواهیم رسید که حتی در صورت مستثنی نمودن ابطال گواهی ثبت اختراع از مقررات مربوط به سلب مالکیت در معاهدات حمایت از سرمایه‌گذاری خارجی، تشخیص نهایی تحقق سلب مالکیت با دیوان داوری است.
Keywords: Elements of indirect expropriation; Foreign investment; Indirect expropriation; Intellectual property; Invalidation of patents; ابطال گواهی ثبت اختراع; حقوق مالکیت فکری; سرمایه‌گذاری خارجی; سلب مالکیت غیرمستقیم; عناصر سلب مالکیت غیرمستقیم

Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

Développement des investissements immatériels dans les entreprises des pays en voie de développement : quelle place pour le conseil d’administration ? - Gonne, Jérôme; Bello, Pascal; Feudjo, Jules Roger (Revue de Recherches en Economie et en Management Africain, 2020)
L’objectif de cet article est d’analyser l’apport des compétences spécifiques des membres du conseil d’administration (CA) au développement des investissements immatériels dans un contexte de marché boursier embryonnaire. Pour conduire cette étude, nous avons utilisé la méthode hypothético-déductive. Ainsi, à partir de la revue de la littérature, nous avons pu formuler trois (03) hypothèses qui ont été testées par la suite. Les données de l’étude ont été collectées auprès d’un échantillon de 78 Sociétés Anonymes opérant au Cameroun. Les résultats obtenus mettent en exergue deux (02) dimensions des compétences des administrateurs qui permettent particulièrement de garantir une information comptable et financière de qualité sur la composante immatérielle et d’améliorer le niveau des investissements immatériels dans ces entreprises.
Keywords: Accounting information; Board of directors; Compétences des administrateurs; Conseil d'administration; Directors' skills; Financial information; Information comptable; Information financière; Intangible investments; Investissement immatériel; Public limited companies; Sociétés Anonymes

The intersection of Public Procurement Law and Policy, and International Investment Law - Dagbanja, Dominic Npoanlari (Transnational Corporations Journal, 2020)
There is substantial scholarship on the limitations that international investment agreements (IIAs) place on States’ authority to regulate in the public interest. An area of fundamental importance that has not received scholarly attention in connection with IIAs is public procurement regulation. Given that public procurement is about the needs of States and their citizens, States would want to retain their authority within municipal public procurement laws to decide with whom to contract to meet those needs, and to pursue socioeconomic and industrial policies through procurement. However, most States are parties to IIAs, which impose obligations on them with respect to the protection of foreign investment. This article explores this seminal issue of whether IIAs stand to limit the authority of States in the implementation of procurement legislation and policies. Based on textual analysis and arbitral case study, it argues that treaty-based standards of investment protection can limit States’ authority on the implementation of methods of procurement (such as national competitive tendering or restricted tendering) and socioeconomic policies in procurement. A question that needs fuller engagement is the extent of conflict between specific IIAs and public procurement laws and policies, either regionally or globally, and how to reconcile conflicting obligations to promote foreign investment and sustainable development. This article provides the foundation for such future research.
Keywords: Foreign (International law); Investments; Methods of procurement; Socioeconomic policies; Sustainable development

L’entrepreneuriat dans le Secteur [In]Formel au Sud-Kivu, en R.D. Congo - Mihigo, Isidore Murhi; Dady, Cool Mangole; Ibale, Douglas Amuli; Elie, Lunanga; Mukulu, Joseph Bahati (Revue de l’Entrepreneuriat et de l’Innovation, 2020)
Since the crises of 1970 and 1980, there has been a remarkable growth in the creation of enterprises in both formal and informal economies. This study attempts to highlight the determinants of the probability of entering the formal sector through an econometric analysis. The data used are based on surveys of 210 SMEs in the in[formal] sector in the city of Bukavu in DR Congo. We find that the probability of entering the formal sector is explained by the entrepreneur’s characteristics (gender and occupied status of employee) and the firm’s characteristics (capital, turnover, and the size of the workforce]. The capital of the company remains the most important constraint that entrepreneurs face to undertake in the formal sector.
Keywords: Bukavu; entrepreneur; formal; informal and sector

Investissement direct étranger et croissance économique en zone CEMAC : Le rôle du capital humain. - Ekodo, Raymond (Revue Marocaine d'Economie, 2020)
Résumé : L’objectif de ce papier est d’évaluer l’effet du capital humain dans la relation qui existe entre l’investissement direct étranger (IDE) et la croissance économique dans les pays de la Communauté Economique et Monétaire de l’Afrique Centrale (CEMAC). Pour y arriver, des estimations économétriques ont été faîtes en utilisant la Méthode des Moments Généralisés (MMG) en panel dynamique des six pays de la zone sur la période allant de 1996 à 2016. Les résultats obtenus montrent que le capital humain n’exerce aucune influence sur la relation  entre l’IDE et la croissance économique dans le cas des pays de la CEMAC, et que la quasi-totalité de ces pays font plutôt face à un problème de la qualité du capital humain. Au regard de ces résultats, des recommandations ont été faites pour une amélioration de la capacité d’absorption des technologies avancées issues des flux entrants d’IDE par les pays hôtes à travers un capital humain au potentiel optimal pour la promotion d’une croissance économique de long-terme dans la zone Mots clés : Capital humain, Investissement Direct Etranger, croissance économique, CEMAC, MMG. The objective of this paper is to assess the effect of human capital in the relationship that exist between foreign direct investment (FDI) and economic growth in the Economic and Monetary Community of Central Africa (EMCCA) countries. To achieve this objective, econometric analyses of the panel data of the six countries for the period 1996 to 2016 have been carried out using the Generalized Methods of Moment (GMM). The result obtained from the analyses show that human capital has no influence on the relationship between FDI and economic growth in the case EMCCA countries, and that instead they face the problem of the quality of human resources. Based on the findings recommendations were made on how to improve the absorptive capacity of advanced technology deriving from FDI by hosts’ countries through human capital of optimal potential for the promotion of long-term economic growth in the zone.Keys words: human capital, foreign direct investment, economic growth, CEMAC, GMM
Keywords: CEMAC; Capital humain; Croissance économique; Economic growth; Foreign direct investment; GMM; Human capital; Investissement Direct Etranger; Investissements; Investments; MMG

Approche analytique de la ventilation des investissements directs étrangers marocains en Afrique: Trifurcation stratégique - Iraqi, Ahmed (Revue Marocaine d'Economie, 2020)
Depuis 2016, le Maroc est devenu le premier investisseur intra-africain. Une telle amplification de ses IDE envers l’Afrique reflète des motivations stratégiques outre-économiques que ne cesse de rappeler les plus hautes instances dirigeantes du royaume. Concomitamment à cela, la diplomatie africaine du Maroc a été remarquablement entreprenante et ce depuis 2013, et plus particulièrement dans le cadre de sa demande de réintégration réussie à l’union africaine, suivie par une seconde demande d’admission au sein de la CEDEAO qui s’est soldée également par un accord de principe favorable. À cet effet, nous nous sommes penchés sur des considérations d’ordre stratégique en mettant au diapason les caractéristiques inhérentes des investissements marocains en Afrique par rapport à une multitude d’enjeux. Dit autrement, nous avons délimité la ventilation stratégique des investissements marocains à la base d’une considération tridimensionnelle, se basant en l’occurrence sur le motif d’ordre économique, l’intérêt géopolitique outre la motivation tendancielle relativement à la prédation économique mondiale dont est victime le continent.
Keywords: Afrique; Banques; FDI; Foreign direct investment; Géopolitique; Investissements; Investissements directs étrangers; Investments; Maroc; Stratégie

Chinese Investment in Ethiopia: Contribution, Challenges, Opportunities and Policy Recommendations - Gebrehiwot, Berihu Assefa; Gebreeyesus, Mulu; Weldesilassie, Alebel Bayrau (PSI Research Report, 2020)
Recognizing the immense potential for greater Chinese investment promotion and its contribution to Ethiopia’s industrialization and acknowledging the gaps, this paper aims to conduct a rigorous research through analysis of secondary sources and qualitative survey of Chinese enterprise doing business in Ethiopia in various sectors. In this regard, the key policy questions that this study tries to answer are ‘the involvement in and the contribution to Ethiopia’s industrialization and the challenges and opportunities they face. Hence, the overall objective of this research will be to (i) assess the trends in Chinese enterprises involvement in Ethiopia’s industrialization for the last decade, (ii) inform both the Chinese government and Ethiopian government on key business barriers and market failures that are constraining Chinese business entry and growth in Ethiopia; (iii) investigate the immense untapped investment potential from China that can be attracted and opportunities that Ethiopia could offer to Chinese investors; and (iv) propose policy options on how to address the challenges and thereby maximize the opportunities to enhance Chinese investment towards Ethiopia’s industrialization.

Zukunftsfähiger internationaler Rechtsrahmen für Investitionen in Afrika - Gramlich, Ludwig (Recht in Afrika, 2020)
The future of sustainable development in Africa and for its growing population will depend on investments which might come mostly from abroad attracted by a favourable investment climate (or ecosystem). It is rather doubtful that the actual ('old') international legal framework for investment-related and investment-specific measures which does hardly create an adequate balance between the interests of all important public as well as private stakeholders would meet the requirement of today and tomorrow. But any alterations or improvements must start from the present state of things. So, this study looks at the different levels and various instruments dealing with traditional standards of investment and investor protection, e.g. BITs und TIPs, and at the activities of global, regional and sub-regional organizations (in particular EU and OHADA). Moreover, new developments at global and regional levels are discussed including trends showing a somewhat specific African approach to investment issues ('Africanization'). Finally, a very important topic, i.e. the relation between investment protection and human rights (of investors and of other people negatively affected by relevant activities), is described and assessed in more detail. A second part of the analysis will turn to elaborating on dispute settlement and enforcement issues since till today, there seems to be a sharp distinction between Investor-State- Dispute Settlement (ISDS) by way of mediation, conciliation and arbitration on the one hand and judicial redress by national courts (of home, host or third States) on the other.

The Effect of IFRS Adoption on Foreign Direct Investment in Africa - Musah, Alhassan; Adjei, Eunice; Ahmed, Ibrahim Anyass (Journal of Applied Accounting and Taxation, 2020)
Adoption of International Financial Reporting Standards (IFRS) is supposed to help enhance comparability of financial statement, improve the quality of financial reporting and accounting information of businesses in a country. This is expected to help improve Foreign Direct Investment (FDI) in the adopting countries. This study examined the effect of IFRS adoption on FDI inflows in Africa. Unlike previous studies that sample both adopting and non-adopting countries, this study sampled only Africa countries that have adopted IFRS to determine whether the adoption has improved FDI inflows. To achieve this objective, 20 African countries that have adopted IFRS were sampled covering a period 1980 to 2015. Data was sourced from The World Bank financial and Economic Data. Control variables such as GDP growth, openness of the economy, government debt and population growth were included in the model. The correlation and regression analysis showed that IFRS adoption has a positive and significant influence on FDI inflows in Africa. On the other hand, open economy, government debt and population growth had a positive and significant association with FDI. Overall, the results show that African countries that want to improve FDI inflows must improve the quality of their reporting environment by adopting IFRS.
Keywords: Africa; FDI; Foreign direct investment; IFRS; IFRS adoption; Investments; Macroeconomic variables

Les facteurs d’attractivité des Investissements Directs Etrangers par les Pays en Développement et l’effet modérateur de la qualité des institutions - El Jazouli, Moutia (International Review of Economics, Management and Law Research, 2019)
L’attractivité des investissements directs étrangers (IDE) a fait l’objet de plusieurs recherches empiriques. Beaucoup d’auteurs se sont intéressés aux facteurs qui expliquent l’afflux de ces investissements sur les pays d’accueil. L’effet d’un facteur d’attractivité des IDE change en effet d’un pays à l’autre. Cette recherche examinera l’effet modérateur de la qualité des institutions légales et gouvernementales du pays d’accueil des IDE de la relation entre ces investissements et les facteurs de leur attraction. Les principaux résultats montrent que plus les politiques gouvernementales sont efficaces, que plus la corruption est réprimée, que plus les lois protègent les investisseurs, l’attractivité des IDE est assurée par le marché financier et par la stabilité politique que l’ouverture commerciale s’améliore. Il n’en reste pas moins que les pays qui ont des institutions de qualité supérieure se trouve plus pénalisés en termes d’attractivité des IDE lorsque le poids fiscal sur les entreprises qui y opèrent s’alourdit et lorsque leur taux de change devient plus flexible.
Keywords: Attractiveness factors; Attractiveness of FDI; Attractivité des EDI; Données du panel; Dynamic model in first differences; Effet modérateur; Facteurs d’attractivité; Institutional quality; Investments; Moderating effect; Modèle dynamique; Panel data; Premières différences; Qualité institutionnelle

L'internationalisation des investissements en droit africain OHADA - Kouamen Tatkam, Tatiana (Lex4 Magazine, 2019)
L'internationalisation 1 fait intervenir les notions d'interdépendance 2 , de transnationalité 3 et même parfois un effet d'absence de frontières depuis que le monde est si intégré qu'il semble parfois impossible d'assimiler ou de relever l'origine d'un produit, d'un service ou de façon plus globale des échanges. L'internationalisation de façon plus sommaire fait planer sur le haut des hémisphères une sorte d'existence globale, de réussite visuelle et partant d'imposition d'un art de vivre. De nos jours, l'internationalisation est recherchée par toute entité dans l'exploitation de ses activités ; laquelle se matérialise la plupart du temps dans le cadre d'une entreprise ou d'une société. Ce dernier cas est l'objet d'une organisation structurée entre une ou plusieurs associés qui décident de mettre en commun des moyens matériels et financiers dans le but de profiter du bénéfice ou de l'économie qui pourrait en résulter 4. Cette dernière, à savoir la société, facilite évidemment la prolifération desdites activités dans les quatre coins du monde. Selon le théorème de Coase 5 , la firme a cet avantage qu'elle permet de rassembler tous les actes de confections d'un produit ou d'un service de façon intégrée sous le contrôle d'une structure pour limiter les dépenses et ainsi pénétrer le marché sans souci insurmontable. L'internationalisation fait également intervenir le nominatif multinational 6 et la question de la nationalité de l'entreprise 7. Mais au-delà de toutes ces notions, elle amène 11 Du point de vue étymologique, l'internationalisation s'appréhende comme suit : Du latin inter, entre, parmi, avec un sens de réciprocité et de natio, naissance, extraction, dérivant de natus, né. L'internationalisation est l'action d'internationaliser ainsi que le résultat de cette action. Le verbe "internationaliser" signifie rendre international, faire en sorte que plusieurs nations ou toutes les nations soient concernées. Sur le plan économique, pan qui nous intéresse le plus, l'internationalisation est une stratégie de développement d'une entreprise au-delà de son marché national d'origine. Elle peut se manifester par l'implantation d'unités de production dans d'autres pays ou la conquête de plusieurs marchés nationaux. Cf

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.

Les efforts de la CNUDCI pour accroitre le niveau de transparence dans l’arbitrage d’investissement - Belhadj, Miriana (Revue de l'ERSUMA, 2018)
Récemment, la Commission des Nations Unies pour le Droit commercial international (CNUDCI) a adopté deux instruments sur la transparence dans l’arbitrage entre investisseurs et États fondé sur des traités. Un Règlement adopté en 2013, prévoit des règles spécifiques pour compléter tout règlement d’arbitrage choisi pour régir un arbitrage conduit sur la base d’un traité d’investissement. Ces règles prévoient notamment, et sous certaines conditions, la publication d’informations et de documents relatifs à l’affaire. Elles permettent aussi que des observations soient présentées par les tiers ou par une partie au traité non partie au litige. Une Convention adoptée en 2014 met en place un mécanisme efficace permettant aux États de prévoir l’application du Règlement sur la transparence à leurs traités d’investissement antérieurs à l’entrée en vigueur du Règlement. À la date de cet article, la Convention compte cinq États parties, dont deux États africains (18 autres États, dont 3 États africains, l’ont signée) et est entrée en vigueur le 18 octobre 2017. Ces efforts de promotion de la transparence dans l’arbitrage d’investissement ont été suivis de discussions au sein de la CNUDCI aboutissant à ce qu’un nouveau groupe de travail au sein de la CNUDCI soit chargé de réfléchir à une possible réforme du système de règlement des différends entre investisseurs et États (RDIE). Dans le cadre de ces réflexions politiques et techniques de haut niveau, la question de la place de la transparence – autre que la transparence procédurale – est récurrente à plusieurs égards et inévitablement au cœur des débats.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CNUDCI; Investissements; Investments; Transparence; Transparency

L’arbitrage comme mode de règlement des différends dans les codes d’investissements des Etats membres de l’UEMOA - Djigle, Doundongue (Revue de Recherches en Economie et en Management Africain, 2018)
Dans le but d’attirer les investissements directs étrangers, les Etats membres de l’UEMOA ont adopté des codes d’investissements destinés à régir les relations entre investisseurs et Etats. Ces codes privilégient l’arbitrage comme mode de règlement des différends. Mais le fondement de cet arbitrage n’est pas le même dans chacun des codes. Certains codes comportent directement dans leur corpus la clause d’arbitrage que l’investisseur peut activer en cas de survenance d’un litige, tandis que d’autres renvoient à des sources extérieures, tel un contrat d’investissement ou un traité bilatéral d’investissement liant l’Etat d’accueil avec l’Etat d’origine de l’investisseur. En outre, dans leur pratique, les Etats de l’UEMOA donnent souvent le choix aux investisseurs entre différentes instances arbitrales. Pourtant, peu de procédures d’arbitrage sont engagées contre ces Etats sur le fondement des codes nationaux d’investissement.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Code des investissements; Etats membres.; Investissements; Investments; Offre d’arbitrage; UEMOA

Factors Influencing Indian Firms Decision Making In Foreign Direct Investment In Africa - Kukreja, Mukta; Joshi, Mahesh Chandra (International Journal of Applied Business and International Management, 2018)
India's economic progress and relations with other developing regions have received much attention, particularly the way in which Indo-African relations have evolved since 2000. This paper aims to put Indian FDI in Africa into perspective and provide some answers on the nature and possible impact of these flows to the continent. The study utilized the International typology offered by Dunning OLI paradigm to identify the important of Location Specific Advantages and how these advantages leads to selection of location for investment purposes by investors The study findings demonstrated that potential market growth, market opportunities and consumer base are the important indicated Indian firms targets Africa to seek new and unexplored markets of Africa. Competitiveness climate is important determinant along with economies of scale, investment incentives and availability of natural resources.
Keywords: African nations; Developing countries; FDI; India; Indo-Afro relations; Investments; Multinational companies; OLI eclectic paradigm

Le règlement par voie d'arbitrage des litiges relatif aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Commission des Nations Unies pour le droit commercial international (CNUDCI); Contrat; Convention d'arbitrage; Exequatur; Investissements; Investments; Jurisprudence arbitrale; Loi nationale; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Règlement des litiges; Sentence arbitrale; Traité de protection des investissements

Foreign Direct Investment and Economic Development in Africa - Adegboye, F. B.; Ojo, Joshua A. T.; Olokoyo, F. O. (Journal of Internet Banking and Commerce, 2017)
Africa unlike other developing regions of the world has experienced declining flows of foreign direct investment (FDI).The flow of FDI is expected to result into gradual reduction in reliance on external borrowed capital and acceleration of economic development. The study examined the declining flow of FDI to the African regions as well as the impact that it has had on economic development of the region, using the proxies of Income per capita, Life expectancy and Education indices. The study made use of pooled data from thirty nine African countries within the period 1993 and 2012.The method of analysis utilized for the study was the fixed effect least-square dummy variable model, employed to estimate the impact of foreign direct investment on economic development for the selected host African countries. The study finds that foreign direct investment is statistically significant in relation to economic development for host African countries. It is therefore recommended that the governments of host countries should consider closely the sectors that FDI flows into, encourage investment domestically in such sectors such that dependence on external financial flows could be reduced, resulting in sustained increases in income, literacy level and hence improved life expectancy which are expected to result into sustained economic development.
Keywords: Economic Development; Foreign direct investment; Host African Countries; Income Per Capital; Investments; Life Expectancy

Comportement des entreprises en matière d’investissements immatériels : état des lieux et déterminants en contexte camerounais - Gonne, Jérôme; Feudjo, Jules Roger (La Revue Gestion et Organisation, 2017)
Résumé Les facteurs de compétitivité des entreprises dans la nouvelle économie ont changé de nature, passant des éléments physiques aux éléments immatériels. L’objectif de cette communication est donc d’analyser les spécificités des entreprises au Cameroun en matière d’investissements immatériels. Les données de l’étude ont été collectées auprès d’un échantillon de 78 entreprises opérant dans divers secteurs d’activité au Cameroun. Les résultats obtenus soulignent que les investissements immatériels font désormais partie intégrante des habitudes des entreprises camerounaises. Quelques actifs issus de ces investissements y trouvent un marché florissant. Cependant, on peut déplorer dans la majorité de ces entreprises un faible niveau d’investissements immatériels et une déficience de la qualité de l’information comptable et financière relative à ce type d’investissements. Nous relevons par ailleurs que, contrairement à l’intensité immatérielle, la qualité de l’information sur les immatériels semble dépendre de certains facteurs caractéristiques de l’entreprise. The factors of competitiveness of companies in the new economy have changed in nature from physical elements to intangible elements. The purpose of this communication is therefore to analyze the specificities of companies in Cameroon relating to intangible investments. The study's data was collected from a sample of 78 companies operating in various industries in Cameroon. The results emphasize that intangible investments are now part of the habits of Cameroonian companies. Some assets from these investments find in Cameroonian context a flourishing market. However, it is regrettable that the majority of these companies have a low level of intangible investment and impairment of quality of accounting and financial information for this type of investment. We further note that, contrary to the intangible intensity, the quality of information on intangibles seems to depend on some characteristic factors of the company.
Keywords: Accounting information; Cameroon; Cameroun; Companies; Entreprises; Information comptable; Intangible investments; Investissements; Investissements immatériels

Intégration régionale et investissements directs étrangers en Afrique - Mama, Hamimida (Revue Interventions économiques, 2017)
Le continent africain, un grand importateur de denrées alimentaires, connait des épisodes de crises alimentaires. En même temps et paradoxalement, les accords étrangers de leasing de terres sont en hausse depuis 2001. Les avantages que les investissements directs étrangers (IDE) procurent ne sont pas automatiques et ne profitent pas de manière égale aux pays d’origine et aux pays d’accueil. Souvent pour ces derniers, quand il s’agit de pays en développement ou des pays les moins avancés, la c...

Investissements d’accord, mais financement d’abord - Zogning Nguimeya, Felix (Revue Interventions économiques, 2017)
Les banques en Afrique subsaharienne ne possèdent toujours pas de système d’informations leur permettant d’accéder au dossier de crédit des opérateurs économiques qui sollicitent un financement. Si les experts, observateurs et investisseurs s’accordent sur le fait que l’heure est résolument à l’Afrique, que son immense potentiel augure des investissements prometteurs, il reste que le continent n’a toujours pas trouvé le véhicule de financement idéal pour soutenir, voire accélérer sa croissanc...

L'Etat dans l'arbitrage d'investissement - Ranjeva, Hery Frédéric (Revue juridique de l'Océan Indien, 2017)

La protection internationale des investissements en République démocratique du Congo à l’aune de l’affaire Patrick Mitchell devant le Centre International pour le Règlement des Différends relatifs aux Investissements (CIRDI) - Djuma Bilali, Lokema Guy-Prosper (KAS African Law Study Library, 2016)

Foreign Direct Investments and Economic Growth of African Regions: A Comparative Study - Igbinosa, Sunday O.; Ikponmwosa, Noruwa Abu (UNILAG Journal of Humanities, 2016)
The paper examines the impact of Foreign Direct Investments (FDIs)on economic growth in the five regions of Africa, as well as identifies their respective drivers of growth. It employs the Ordinary Least Squares (OLS) multiple regression analysis to examine the relative impact of Foreign Direct Investments, balance of payments, trade openness, technology and quality of labour force on economic growth in each of the five regions between 1980 and 2012. The study finds that foreign Direct Investments (FDIs) have no significant impact on economic growth in the five regions of Africa. The impact of FDI on growth is positive in Eastern, Middle and Western Africa but negative in Northern and Southern Africa. Similarly, there are differentials in the drivers of growth in the five regions. While trade openness is a negative driver of growth in all regions of Africa except in Northern Africa, both balance of payments and quality of labour force have mixed impacts on economic growth in Africa. In addition, technological progress impacted growth in Middle, Southern Africa and Western Africa but it appears that lack of it retarded growth in Eastern and Northern Africa. The study calls for policy reform frameworks that encourage and boost foreign Direct Investment flows to all regions of Africa, particularly Direct Investments in critical sectors of the economies, as well as check the negative effects of foreign Direct Investments. Furthermore, it recommends that regional economic blocks in Africa should be resuscitated and supported to develop and promote intra-Africa trade and Investments.
Keywords: African regions; Drivers of growth; Economic growth; FDI; Foreign direct investment; Investments

Policy Options for Promoting Foreign Direct Investment in the Least Developed Countries - Sauvant, Karl P.; Mallampally, Padma (Transnational Corporations Review, 2015)
Foreign direct investment (FDI) plays an important role in the world economy and has the potential to contribute towards accelerating the process of economic growth and sustainable development in the least developed countries (LDCs). The paper provides a brief overview of recent trends and patterns in FDI flows to the LDCs, and then takes stock of the policies, programmes and measures pursued by host and home countries and by international organizations to stimulate FDI flows to LDCs and increase their benefits for these countries. It then lays out a number of policy proposals on how flows to LDCs, and the benefits associated with them, can be enhanced. Finally, it outlines some options for international action to strengthen such efforts – proposals and options that are also relevant to other developing countries.
Keywords: Development; Foreign direct investment; Least Developed Countries; policy options

The effects of the South African anti-dumping and competition measures upon foreign direct investment - Sibanda, Omphemetse S. (Journal of Business and Retail Management Research, 2014)
Since the dawn of democracy South Africa has embarked in a process of dismantling protectionist business and trade policies, and made the country’s stream of commerce one of the preferred globally. The country’s sound competition and trade policies, natural resource endowments, market size and regional influence, attracted foreign businesss and foreign direct invetsment (FDI). Equally the country has been under pressure to protect the domestic industries from injurious competition and business, through sector specific laws, anti-dumping and countervailing duties laws, investment and competition regime. The concern has been the likilelihood of the introduction of trade and competition barriers, and the allienation of FDI. This paper critically examines the impact the country’s antidumping and competition law and practice upon foreign direct investment. Domestic industries have never been shy to file anti-dumping and anti-competition suits against foreign companies, sometimes even when there might be a public outcry. Relevant examples of these suits include the famous Wal-Mart anti-competition case, and recently the Brazilian frozen fowl meat anti-dumping case.
Keywords: Anti-Dumping; Competition; Consumers; Divestment; Domestic Industry; Investments; Protection; Tariffs

Investment Protection in the Framework of the Treaty of Harmonizing Business Law in Africa (OHADA) - Houanye, Paulin; Shen, Sibao (Beijing Law Review, 2013)
A few years ago, African contribution of the world trade was only around 2%. The investors, except those who are exploiting natural resources, never want to dare dispensing their fund in Africa. The reason of this situation was very simple. The majority of investors denounce the juridical insecurity and also the political preponderance across the African continent. With human and natural resources abundant, Africa is regarded as a continent equipped with a great potential of development. The years of independences in Africa saw being born in many States, of the organizations trying to solve these difficulties and to reinforce their capacities by the constitution of international organizations acting in all the fields. But it is only in the year 1990; some organizations appeared in the continent and knew of real rise thanks to the liberal and democratic economic policies. This article wishes to present an assessment of seventeen years implementation of the African Harmonization of Business Law Treaty of 1993. Firstly, it will describe the system from an institutional point of view and hence from a normative point of view. Secondly, during the course of this essay, there will be a focus on analysis of OHADA’s laws, its system and its potential impact. In addition, the article will concentrate on OHADA’s appropriateness in the business sector and necessary guarantees it must offer for a successful investment partnership with foreign investment.
Keywords: African Development; Harmonization; Harmonization Business Law; Investment Law; Investments; Regional integration; Rule of Law

Les problèmes juridiques relatifs à la communautarisation du droit des investissements dans l’espace UEMOA - Ouedraogo, Séni Mahamadou (Annuaire Français de Droit International, 2012)
Le développement du droit communautaire en Afrique de l’Ouest couvre aujourd’hui un large champ qui s’étend aux investissements demeurés au lendemain des indépendances des États africains dans le périmètre de leur souveraineté. Les enjeux actuels du droit international des investissements, en raison des exigences de la mondialisation des économies, ont contraint les États de l’espace CEDEAO et UEMOA, importateurs de capitaux, à faire converger leur réglementation des investissements afin de favoriser leur attractivité et d’en tirer le meilleur parti. La difficulté d’un tel objectif réside dans la nécessité d’arriver à concilier leurs intérêts avec ceux des investisseurs, qui ne sont pas toujours convergents. The development of community law in West Africa nowadays covers a wide field extending to investments which, in the aftermath of independence, remained within the scope of sovereignty of African states. The current challenges of international investment law, because of the requirements of economic globalisation, have compelled ECOWAS and WAEMU countries, as importers of capital, to ensure convergence of their investment regulations so as to make them more attractive and to get the most out of them. The difficulty of such an objective lies in the need to successfully reconcile their interests with those of investors, which do not always converge.

Revisiting the Depoliticization of Investment Disputes - Schneiderman, David (Yearbook on International Investment Law and Policy, 2011)
The chapter challenges claims about depoliticization in two different aspects. The first examined claim is that home states are disenfranchised from pursuing investment claims once they are lodged with ICSID. Is it the case that home states simply stay home? This chapter examines instances where home states may have played a role in investment disputes between contracting states. What the record generally reveals, however, is that home states involve themselves in disputes where ICSID hearings are imminent but not yet in play. The second, broader, reading of depoliticization maintains that disputes now are resolved without recourse to lowly politics but to ‘higher’ law. This more extravagant claim is vulnerable to the critique that investor-state dispute resolution is not emptied of political content but, instead, spills over with politics. As the regime implicates the capacity of public authority to act in a wide variety of regulatory contexts, the separation of law from politics is hard to credibly maintain. Not only are investor-state disputes embedded within regimes of political discourse and political power, the ambit of investment arbitrator discretion is so capacious that it can be said of arbitrators, as it has been said of the U.S. Supreme Court, that they can sensibly be regarded as political actors.